2022
DOI: 10.4314/ahs.v22i4.73
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and factors associated with stunting among under- five-year children: a cross-sectional population-based study in Rwanda of the 2014-2015 demographic and Health Survey

Abstract: Background: Globally, stunting affects 159 million Under-five-years-old (U-5) children. Stunting affects the physical, mental, and cognitive development of children increasing the risk of suffering and death. This paper aimed to determine the predictors and factors associated with stunting among under-five children in Rwanda.Methods: We retrieved data from the Rwanda Demographic and Health Survey (RDHS) 2014-2015 data set. A sample of 3599 U-5 eligible children with complete and valid anthropometric data was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Furthemore, it is also consistent with the research conducted by Bigirimana [ 21 ] that revealed a significant correlation between stunting and family planning, as well as household size in Rwanda. The findings of this study are also in line with earlier research that showed a higher proportion of stunted children resided in rural areas than in urban areas [ 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthemore, it is also consistent with the research conducted by Bigirimana [ 21 ] that revealed a significant correlation between stunting and family planning, as well as household size in Rwanda. The findings of this study are also in line with earlier research that showed a higher proportion of stunted children resided in rural areas than in urban areas [ 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the Ministry of Health has recently alluded to the fact that there are zero case of Ebola in the country: good news! We end the treatise with papers on childhood illnesses [70][71][72][73][74] and health systems [75][76][77]…”
mentioning
confidence: 99%